Gold-based drug encapsulation within a ferritin nanocage: X-ray structure and biological evaluation as a potential anticancer agent of the Auoxo3-loaded protein. Issue 61 (21st June 2016) - Ferraro, Giarita; Monti, Daria Maria; Amoresano, Angela; Pontillo, Nicola; Petruk, Ganna; Pane, Francesca; Cinellu, Maria Agostina; Merlino, Antonello
Abstract : Auoxo3, a cytotoxic gold(iii ) compound, was encapsulated within a ferritin nanocage. Abstract : Auoxo3, a cytotoxic gold(iii ) compound, was encapsulated within a ferritin nanocage. Inductively coupled plasma mass spectrometry, circular dichroism, UV-Vis absorption spectroscopy and X-ray crystallography confirm the potential-drug encapsulation. The structure shows that naked Au(i ) ions bind to the side chains of Cys48, His49, His114, His114 and Cys126, Cys126, His132, His147. The gold-encapsulated nanocarrier has a cytotoxic effect on different aggressive human cancer cells, whereas it is significantly less cytotoxic for non-tumorigenic cells.